IDENTIFIKASI FAKTOR YANG MEMPENGARUHI IBU NIFAS MENGKONSUMSI VITAMIN A - Putri Sari, Yemmy; Dimas Ayub, Agis; Tedengki, Rein; Ville Rizal, Rossy; Palola, Jessldryn (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background: Vitamin A plays a crucial role in vision, immune system function, and reproduction, which is especially significant during pregnancy and breastfeeding. Deficiencies can lead to severe health issues for both mothers and infants. Method: This study employs a non-experimental, quantitative, analytic design using a cross-sectional approach, surveying postpartum mothers at Puskesmas Karya Maju, Keluang Musi Banyuasin, to identify factors affecting Vitamin A consumption. Results: Analysis revealed that younger mothers (age 20-35) are significantly less likely to consume Vitamin A, showing an odds ratio (OR) of 9.6 (p=0.013). Additionally, education level plays a significant role; mothers with lower education levels were 1.07 times more likely not to consume Vitamin A (p=0.011). A negative attitude was linked to a 10.3 times higher likelihood of non-consumption (p=0.014). While knowledge showed a positive correlation, it did not reach statistical significance (p=0.068). Conclusion: Educational interventions are necessary to boost Vitamin A consumption among postpartum mothers, particularly targeting younger demographics and those with less education. This will help alleviate Vitamin A deficiency, improving maternal and child health outcomes. Keywords: Vitamin A, postpartum nutrition, maternal health, education, public